Penerapan “Pembelajaran APIK” untuk Meningkatkan Keaktifan dan Hasil Belajar IPA di MTs Negeri 1 Bantul - Asih Budiati (Jurnal Pendidikan Madrasah, 2020)
This research is a best practice aimed at knowing the influence of APIK learning (Actualisation, Presentations, Initiatives, and Quizzes) in overcoming the low physical preparation and material of students as well as their participation in conducting the learning activities of science class VII-D MTs Negeri 1 Bantul school year 2019-2020, with the expectation of activities and learning outcomes increased. The implementation of APIK learning is learning that uses the actualization and presentation stage at the beginning of learning, the initiative stage and the quiz at the core of learning. This research uses qualitative methods of descriptive including observation, documentation, interviews, and test learning outcomes. The results show that APIK learning has a positive effect on the active and student learning outcomes. This was demonstrated by increased positive activity during the learning of 100% of students listening to teacher explanations, 93.5% of students noted the material learned and 80.6% of students asked. An increase in the average student's learning outcomes from 66.29 to 81.90. APIK methods can be applied in the learning process in class.